2018
DOI: 10.1016/j.nima.2018.02.091
|View full text |Cite
|
Sign up to set email alerts
|

Design study of a photon beamline for a soft X-ray FEL driven by high gradient acceleration at EuPRAXIA@SPARC_LAB

Abstract: We are proposing a facility based on high gradient acceleration via x-band RF structures and plasma acceleration. We plan to reach an electron energy of the order of 1 GeV, suitable to drive a Free Electron Laser for applications in the so called water window (2-4 nm). A conceptual design of the beamline, from the photon beam from the undulators to the user experimental chamber, mainly focusing on diagnostic, manipulation and transport of the radiation is presented and discussed. We also briefly outline a user… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…We plan to monitor the trajectory of the photons with Beam Position Monitors (BPMs) along the line. These BPMs are composed of four metallic blades collecting a drain current from intercepting the very edges of the beam [20] in order to have minimal diffraction and absorption effects. We expect to have a spatial resolution of approximately two microns RMS [30] from the reference.…”
Section: Beam Transport and Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…We plan to monitor the trajectory of the photons with Beam Position Monitors (BPMs) along the line. These BPMs are composed of four metallic blades collecting a drain current from intercepting the very edges of the beam [20] in order to have minimal diffraction and absorption effects. We expect to have a spatial resolution of approximately two microns RMS [30] from the reference.…”
Section: Beam Transport and Controlsmentioning
confidence: 99%
“…The first designed FEL beamline, called AQUA [20][21][22], will operate in the water window at 3-4 nm, as required by the EuPRAXIA design study, according to the beam parameters reported in Table 1. This beamline will use the full undulator length available to the project and very high quality electron beams.…”
Section: Introductionmentioning
confidence: 99%
“…In the downstream tunnel a 40 m long undulator hall is shown, where the undulator chain will be installed [16]. Further downstream after a 12 m long photon diagnostic section [17] the users hall is shown [18]. Additional radiation sources as THz and γ-ray Compton sources are foreseen in the other shown beam lines.…”
Section: The Eupraxia@sparc_lab Conceptmentioning
confidence: 99%
“…The unique FEL features (energy range, time resolution and brilliance) can be exploited in several branches of physics, chemistry, material science and biology. In this paper, we describe the main experimental lines that can be investigated at the EuPRAXIA@SPARC_LAB FEL [9,10] ( Figure 1). The EuPRAXIA@SPARC_LAB FEL will provide photon pulses with high intensity, up to 10 12 photons/pulse, down to a wavelength of about 3 nm, in the so called "water window".…”
Section: Introductionmentioning
confidence: 99%